97.3k views
4 votes
-9m+10(m+3)=-7(m-10)Solve for m

User Msanjay
by
5.7k points

1 Answer

7 votes

Answer:

m = 5

Step-by-step explanation:

The given expression is


-9m+10(m+3)=-7(m-10)

First, we need to apply the distributive property, so


\begin{gathered} -9m+10(m)+10(3)=-7(m)-7(-10) \\ -9m+10m+30=-7m+70 \\ 1m+30=-7m+70 \end{gathered}

Then, subtract 30 from both sides


\begin{gathered} m+30-30=-7m+70-30 \\ m=-7m+40 \end{gathered}

Add 7m to both sides


\begin{gathered} m+7m=-7m+40+7m \\ 8m=40 \end{gathered}

Finally, divide both sides by 8


\begin{gathered} (8m)/(8)=(40)/(8) \\ \\ m=5 \end{gathered}

Therefore, the answer is m = 5

User Jltrem
by
6.7k points